THE IMPLEMENTATION OF PEER FEEDBACK STRATEGY FOR WRITING INSTRUCTION AT THE FIRST SEMESTER OF WRITING 1 CLASS AT MUHAMMADIYAH UNIVERSITY OF METRO - Lilis Sholihah (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2015)
ABSTRACTPeer feedback is one alternative strategy that can be used by the teacher/lecturer when conducting teaching writing. The procedure of the strategy enables the students to work cooperatively in a group/peer. The students can give comments on their classmates’writing for better quality writing. They also can learn how to revise their own text based on comments from peers. Peer feedback can be one solution to minimize the errors made by the students in their writing. The implementation of peer feedback in the classroom offers beneficial effects for the students either as the writers or as the readers. This method is appropriate design in improving the students writing ability.